Internalization of Cultural Legal Values among Elementary Students in Kuala Lumpur - Muhammad Daffa Dhiya Ulhaq; Ertika Fitri Listanti; Zainal Arifin; Emi Puasa Handayani4 (Penerbit Goodwood, 2026)
Purpose: This study examines how cultural legal values are internalized among elementary school students in Kuala Lumpur, and how this process strengthens their awareness of cultural heritage rights as part of their national identity. Research Methodology: The study was conducted at Sanggar Bimbingan Pantai Dalam through an International Community Service Program involving 15 upper-grade elementary students (aged 10–12). It applied an educative-participatory approach within a juridical-normative framework, using culture-based learning materials, multimedia resources, discussions, simulations, and case exercises. Data were obtained from pre- and post-tests, complemented by observations and reflections, and analyzed descriptively to assess changes in learning outcomes. Results: The findings indicate an improved understanding of cultural heritage and greater awareness of cultural rights, reflected in higher post-test scores and more active participation. Students also demonstrated stronger moral responsibility for cultural preservation and increased tolerance in a multicultural context. Conclusions: This study concludes that integrating cultural legal values through structured classroom learning, co-curricular activities, and teacher role modeling effectively strengthens students’ knowledge and character development. This approach supports the development of legal awareness and respect for cultural diversity from an early age. Limitations: This study had a small sample size, single-institution focus, absence of a control group, brief implementation period, and evaluation methods that emphasized cognitive outcomes. Future research should involve broader samples, longitudinal designs, control groups, and more comprehensive assessment tools. Contributions: This study contributes to legal, multicultural, and character education by offering a practical model for value-based cultural learning in elementary schools.